Cardiac and Pulmonary Ultrasound for Diagnosing TRALI - J. I. Alonso-Fernández; J. R. Prieto-Recio; C. García-Bernardo; I. García-Saiz; J. Rico-Feijoo; C. Aldecoa (Case Reports in Critical Care)
Unexpected acute respiratory failure after anesthesia is a diagnostic challenge: residual neuromuscular blockade, bronchial hyperresponsiveness, laryngospasm, atelectasis, aspiration pneumonitis, and other more uncommon causes should be taken into account at diagnosis. Lung ultrasound and echocardiography are diagnostic tools that would provide the differential diagnosis. We report a suspected case of a transfusion related acute lung injury (TRALI) following administration of platelets. The usefulness of lung and cardiac ultrasound is discussed to facilitate the challenging diagnosis of the acute early postoperative respiratory failure.